Neurophysiological visual assessment in patients with idiopathic intracranial hypertension: visual evoked potential and multifocal field electroretinography - Marwa A. Elgaly; Hanan Hosny; Hala R. El Habashy; Mona Hussein; Rehab Magdy; Rehab Elanwar (BMC Neurology, 2023)
Abstract Background Determining the cause of visual deterioration in idiopathic intracranial hypertension (IIH) patients is of clinical necessity. This study aimed to study the effect of chronic increased ICP on the retina and optic nerve through objective electrophysiological measures in chronic IIH patients. Methods Thirty patients with chronic IIH and thirty age and sex-matched healthy controls were included in this study. Papilledema grade and CSF pressure were evaluated in the patients’ group. Both groups were submitted to visual evoked potentials (VEP) and multifocal electroretinogram (mfERG). Result The mean value of P100 latencies of the right and left on two check sizes, 1 deg and 15ṁ in chronic IIH patients, was significantly delayed than controls (P-value < 0.001 for each). Chronic IIH patients showed a significantly lower amplitude of the right and left R1, R2, R3, R4 & R5 compared to controls (P-value < 0.001, < 0.001) (P-value < 0.001, < 0.001) (P-value < 0.001, < 0.001) (P-value < 0.001, = 0.001) (P-value = 0.002, < 0.001), respectively. Also, patients showed a significantly delayed peak time of the right and left R1 and R2 compared to controls (P-value < 0.001, < 0.001) (P-value = 0.001, = 0.009), respectively. There was a significant positive correlation between each of CSF pressure and papilledema grade with right and left PVEP latencies. In contrast, there was no statistically significant correlation between either CSF pressure or papilledema grade and PVEP amplitudes in both eyes. Conclusion In chronic IIH patients, both optic nerve dysfunction and central retinal changes were identified, supported by VEP and the mfERG findings.